2019
DOI: 10.3389/fpsyg.2019.02311
|View full text |Cite
|
Sign up to set email alerts
|

Residential Mobility, Family Structure, and Completion of Upper Secondary Education – A Registry-Based Cohort Study of the Norwegian Adolescent Population

Abstract: Background:Longitudinal studies exploring the complex interplay between family structures and residential mobility on educational achievement and failure are lacking. We investigate the interplay between the number of residential moves during late childhood, parental education level, family living situation, and the probability of completing upper secondary education.MethodologyDetailed longitudinal data for a random sample of 30% of the entire Norwegian population born 1982 to 1989 (N = 121,247) and informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Norway is a welfare state, and education, including university, is free. However, previous studies have shown that parent's education and employment seem to affect their children's probability of completing upper secondary school and choice of educational track, both in Norway and other Nordic welfare states like Finland (Koivusilta et al, 2013;Bania et al, 2015;Kallio et al, 2016;Haugan and Myhr, 2019), demonstrating that choice of career is affected by socioeconomic background.…”
Section: School Functioning and Educational Aspirationsmentioning
confidence: 95%
“…Norway is a welfare state, and education, including university, is free. However, previous studies have shown that parent's education and employment seem to affect their children's probability of completing upper secondary school and choice of educational track, both in Norway and other Nordic welfare states like Finland (Koivusilta et al, 2013;Bania et al, 2015;Kallio et al, 2016;Haugan and Myhr, 2019), demonstrating that choice of career is affected by socioeconomic background.…”
Section: School Functioning and Educational Aspirationsmentioning
confidence: 95%